2014
DOI: 10.4187/respcare.02913
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate Discharge on Bronchodilators and Acid-Blocking Medications After ICU Admission: Importance of Medication Reconciliation

Abstract: BACKGROUND: Previous studies suggest that some medications, including proton pump inhibitors and ␤-agonist inhalers, are administered to hospitalized patients and sometimes continued without indications. Medication reconciliation has been offered as one mechanism to reduce the frequency of such medication errors and is now mandated by the Joint Commission (NPSG.03.06.01). We hypothesized that (1) ␤ agonists and acid-blocking medications are prescribed following critical illness without indications, and (2) med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
81
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(83 citation statements)
references
References 22 publications
2
81
0
Order By: Relevance
“…In one study, discontinuation of a statin or antiplatelet medication showed an increased risk of death, hospital admission and emergency department visit up to 1 year after hospital discharge 1. Medications commenced in ICU were also found to have been continued unnecessarily which is also consistent with previous studies 4 5…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In one study, discontinuation of a statin or antiplatelet medication showed an increased risk of death, hospital admission and emergency department visit up to 1 year after hospital discharge 1. Medications commenced in ICU were also found to have been continued unnecessarily which is also consistent with previous studies 4 5…”
Section: Discussionsupporting
confidence: 75%
“…When patients are critically ill, their chronic drug therapies are frequently withheld in the ICU but are often, inappropriately, not restarted 2 3. Furthermore, new therapies are often commenced, which may be unnecessary in the long term, such as drugs prescribed for stress ulcer prophylaxis and antipsychotics prescribed for delirium 4 5. The care of the complex and dynamic physiology of these patients is made more challenging by frequent transitions in care across the healthcare system, and poor communication at the time of discharge 6 7…”
Section: Introductionmentioning
confidence: 99%
“…Other classes of medications such as acid suppressive agents (proton pump inhibitors, histamine receptor antagonists) and albuterol are continued after discharge from the Intensive Care Unit 3,4 and up to half of potentially inappropriate medications in the elderly on discharge from the hospital were initiated in the ICU. 10 Pronovost and colleagues identified that the transition of care from the Intensive Care Unit to lower levels of care place patients at increased risk for errors in medication therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Other classes of medications, including inhaled bronchodilators and proton pump inhibitors, are frequently started during hospitalizations and continued following discharge, many times inappropriately 3,4 . When combined with the multitude of other factors that contribute to medication management in transitions of care, high-risk medications such as antipsychotics may also be continued inappropriately.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several studies evaluating medication‐related interventions during these transitions. These interventions included deprescribing of ICU‐initiated medications such bronchodilators, atypical antipsychotics, and stress ulcer prophylaxis, as well as re‐initiation of home medications 9‐12 . Therefore, it is crucial to review patients' medication lists to ensure they are receiving appropriate medications during each transition of care.…”
Section: Introductionmentioning
confidence: 99%